2019
DOI: 10.1111/cas.14193
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin‐Fc chimera protein matrix enhances cancer stem‐like properties and induces mesenchymal features in colon cancer cells

Abstract: Cancer stem cells (CSC) are a subpopulation of tumor cells with properties of high tumorigenicity and drug resistance, which lead to recurrence and poor prognosis. Although a better understanding of CSC is essential for developing cancer therapies, scarcity of the CSC population has hindered such analyses. The aim of the present study was to elucidate whether the E‐cadherin‐Fc chimera protein (E‐cad‐Fc) enhances cancer stem‐like properties because studies show that soluble E‐cadherin stimulates human epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…E-cadherin is a calcium-dependent transmembrane cell adhesion molecule, which plays a key role in maintaining epithelial polarity and integrity. Previous studies proved that loss of E-cadherin could promote the invasion and metastasis of tumor, which was also related to poor prognosis in patients with breast, colon, and other cancers [ 26 , 27 ]. The results from the current study showed that ANKRD22 contributed to breast cancer progression, indicating that it might act as a potential marker for the therapy of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is a calcium-dependent transmembrane cell adhesion molecule, which plays a key role in maintaining epithelial polarity and integrity. Previous studies proved that loss of E-cadherin could promote the invasion and metastasis of tumor, which was also related to poor prognosis in patients with breast, colon, and other cancers [ 26 , 27 ]. The results from the current study showed that ANKRD22 contributed to breast cancer progression, indicating that it might act as a potential marker for the therapy of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the EGFR pathway also contributes to the chemoresistance of CRC by inducing EMT and enriching the CSC population [ 249 ]. Similarly, the reduced expression of this pathway’s inhibitors, such as VPS33B, has been associated with poorer prognosis in patients and increased resistance to oxaliplatin in vitro and in vivo [ 236 ].…”
Section: Phenotype Transition (Moc-7)mentioning
confidence: 99%
“…The oncogenic role of SOX9 is related to several cell signaling pathways, such as the TGFβ/Smad, Notch and Wnt/β-catenin pathways (Li and Neaves, 2006;Abdul Khalek et al, 2010). Studies have confirmed that SOX9-overexpressing cancer cells are resistant to oxaliplatin (Anuja et al, 2019;Qian et al, 2019;Abad et al, 2020;Das et al, 2020). However, the underlying mechanism of SOX9 in resistance to oxaliplatin is still unclear.…”
Section: Introductionmentioning
confidence: 99%